1991
DOI: 10.1023/a:1015836720294
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The clearance and volume of distribution of five human proteins (recombinant CD4, CD4 immunoglobulin G, growth hormone, tissue-plasminogen activator, and relaxin) in humans and laboratory animals were analyzed as a function of body weight using allometric scaling techniques. These proteins cover a 16-fold range of molecular weight (6 to 98 kD), are produced by recombinant or synthetic methods, and may be cleared by different mechanisms. The analyses revealed that the clearance and volume data for each protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…Positive results from human clearance prediction of macro-molecule drugs using allometric scaling have already been reported by several groups (Mordenti et al, 1991, Mahmood, 2004, Mahmood, 2009b, Ling et al, 2009, Wang and Prueksaritanont, 2010). Mordenti et al demonstrated reasonable accuracy in predicting human clearance and volume of distribution using interspecies scaling for five protein drugs with molecular weights ranging from 6 to 98 kDa (Mordenti et al, 1991).…”
Section: Introductionmentioning
confidence: 74%
“…Positive results from human clearance prediction of macro-molecule drugs using allometric scaling have already been reported by several groups (Mordenti et al, 1991, Mahmood, 2004, Mahmood, 2009b, Ling et al, 2009, Wang and Prueksaritanont, 2010). Mordenti et al demonstrated reasonable accuracy in predicting human clearance and volume of distribution using interspecies scaling for five protein drugs with molecular weights ranging from 6 to 98 kDa (Mordenti et al, 1991).…”
Section: Introductionmentioning
confidence: 74%
“…For example, preparations of PEG-adenosine deaminase are efficacious when given weekly, compared with the daily injections of unmodified adenosine deaminase for the treatment of severe combined immune deficiency disease in children (22). Because proteins are cleared faster in rodents than in humans (23), it is possible that PEG-5-hGH given at bi-weekly or even monthly intervals could have efficacy comparable with daily injections of hGH in humans.…”
Section: Figmentioning
confidence: 99%
“…t 1/2β may be predicted by indirect methods which involve a reasonable prediction of the volume of distribution and clearance (t 1/2β = 0.693 × V dss /CL) or MRT (t 1/2β = MRT/1.44). However, Mordenti et al [121] who analyzed the clearance and volume of distribution of five human proteins (recombinant CD4, CD4 immunoglobulin G, growth hormone, tissueplasminogen activator, and relaxin) in laboratory animals as a function of body weight using allometric scaling technique.…”
Section: Discussionmentioning
confidence: 99%